The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution I. Family Halictidae, genus Lasioglossum Curtis, 1833 - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2018)
The type specimens of Lasioglossum Curtis, 1833 deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Primary types of 69 taxa are illustrated and detailed information is provided (taxa include 33 described by F. Morawitz; 16 by P. Blüthgen; 15 by Yu. Pesenko (one of them with N. Davydova); four by E. Eversmann; and one by T.D.A. Cockerell). Lectotypes are designated here for the following eleven nominal taxa: Halictus anguliceps Morawitz, 1893, H. corvinus Morawitz, 1877, H. debilis Morawitz, 1893, H. glabriusculus Morawitz, 1872, H. gussakovskii Blüthgen, 1929, H. hyalinipennis Morawitz, 1876, H. morbillosus orientis Cockerell, 1924, H. popovi Blüthgen, 1931, H. porcus Morawitz, 1872, H. puncticollis Morawitz, 1872, and H. truncaticollis Morawitz, 1877.